CONCEPTUAL DESIGN OF BIRD-LIKE UNMANNED AERIAL VEHICLE FOR BIRD PEST CONTROL - Buyung Junaidin; Dwi Hartini; Santo Herlambang (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2020)
Finch (Lonchura) pest bird becomes a serious problem for rice-plant farmers when entering harvest period because it could make crop yields decreases or even crop failure. There are many method have been done for pest bird control but almost all of those are not effectives. Bird-like unmanned aerial vehicle is proposed as an alternative solution to control pest bird. The aim of this research is to do conceptual design of unmanned aerial vehicle which look like predator bird for pest bird control in farm area. The predator bird which means is black eagle (Ictinaetus Malaiensis) which is one of natural predators of small birds including finch family. Conceptual design of bird-like unmanned aerial vehicle follows general design process of aircraft with some simplification. Method of design adopt to Raymer’s method and sketching of black eagle planform especially wings and tail. The design results an unmanned aerial vehicle look like black eagle with cruise speed  is 10m/s and operational altitude 120m above sea level. From aerodynamics analysis shows that bird-like unmanned aerial vehicle which have designed fill lift requirement at angle of attack  3o and longitudinal static stability criteria.